Բաժնետոմսերի նախնական հրապարակային առաջարկը (IPO) որպես ԼՂՀ արժեթղթերի շուկայի զարգացման առաջնահերթ ուղղություն - Սուսան Աբկարի Ավետիսյան (ՀՀ ԳԱԱ հրատ.)
Приключение финансовых ресурсов в ходе IPO позволяет компании необходимые для развития деятельности активы, которые не могут быть получены за счет внутренних ресурсов и преобретение которых нецелесообразно осуществять за счет привлечения кредитов. The attraction of financial resources during the IPO allows the company to acquire assets necessary for the development of activities that cannot be acquired via internal resources and the acquisition of which is not sensible to implement due to the credits extended to companies. For the economic actors in Armenia and Artsakh, the market of public securities is a relatively new phenomenon, due to the predominance of bank lending in the financial market of the Republic of Armenia.
Keywords: Հասարակական գիտություններ; Տնտեսագիտություն; Ֆինանսներ